Screening of wheat genotypes for cadmium resistance (Experimental biology, 2019)
Various genotypes of winter wheat in East Kazakhstan agrocenoses were studied to assess the accumulation of cadmium. It is shown that the amount of cadmium exceeding the MPC in the soil, its content in the grain exceeds the MPC for seeds.  The study also revealed significant differences in cadmium accumulation by genotype. Screening of various genotypes of winter wheat for resistance to cadmium in the laboratory revealed resistant and sensitive to cadmium forms of winter wheat.